The Socio-Legal Lab: An Experiential Approach to Research on Law in Action - Siddharth Peter de Souza; Lisa Hahn (Open Press Tilburg University, 2022)
The Socio-Legal Lab: An Experiential Approach to Research on Law in Action” is an interactive workbook for socio-legal research projects.~It employs the idea of a “lab” as a space for interactive and experiential learning. As an introductory book, it addresses researchers of all levels who are beginning to explore interdisciplinary research on law and are looking for guidance on how to do so. Likewise, the book can be used by teachers and peer groups to experiment with teaching and thinking about law in action through lab-based learning. The workbook~is designed to accompany and inspire researchers on their way through a socio-legal research project. It thus covers themes and questions that may arise in the research process, ranging from socio-legal theory to methods and academic communication. While working through this content in an interactive manner, our aim is to empower the reader into thinking more creatively about their methods, while at the same time demystifying them.
Keywords: 330